Brandwashed : tricks companies use to manipulate our minds and persuade us to buy - Lindström, Martin, 1970- (New York : Crown Business, 2011)
In this shocking, no-holds-barred expose, the author draws on more than 20 years spent in the back rooms and board rooms to reveal all the manipulative ways marketers and advertisers tap into our most deeply seated fears, vulnerabilities, impulses, dreams, and desires, all in the service of taking our dollars. A marketing visionary, he has been on the front lines of the branding wars for over twenty years. Here, he turns the spotlight on his own industry, drawing on all he has witnessed behind closed doors, exposing for the first time the full extent of the psychological tricks and traps that companies devise to win our hard-earned dollars. Picking up from where Vance Packard's bestselling classic, The Hidden Persuaders, left off more than half-a-century ago, this book reveals: New findings that reveal how advertisers and marketers intentionally target children at an alarmingly young age, starting when they are still in the womb! Shocking results of an fMRI study which uncovered what heterosexual men really think about when they see sexually provocative advertising (hint: it isn't their girlfriends). How marketers and retailers stoke the flames of public panic and capitalize on paranoia over global contagions, extreme weather events, and food contamination scares. The first ever neuroscientific evidence proving how addicted we all are to our iPhones and our Blackberrys (and the shocking reality of cell phone addiction, it can be harder to shake than addictions to drugs and alcohol). How companies of all stripes are secretly mining our digital footprints to uncover some of the most intimate details of our private lives, then using that information to target us with ads and offers "perfectly tailored" to our psychological profiles. How certain companies, like the maker of one popular lip balm, purposely adjust their formulas in order to make their products chemically addictive. What a 3-month long guerilla marketing experiment, conducted specifically for this book, tells us about the most powerful hidden persuader of them all. This searing expose introduces a new class of tricks, techniques, and seductions, the hidden persuaders of the 21st century, and shows why they are more insidious and pervasive than ever.
A brand detox -- Buy buy baby: when companies start marketing to us in the womb -- Peddling panic and paranoia: why fear sells -- I can't quit you: brand addicts, shopaholics, and why we can't live without our smart phones -- Buy it, get laid: the new face of sex (and the sexes) in advertising -- Under pressure: the power of peers -- Oh, sweet memories: the new (but also old) face of nostalgia marketing -- Marketers' royal flush: the hidden powers of celebrity and fame -- Hope in a jar: the price of health, happiness, and spiritual enlightenment -- Every breath you take, they'll be watching you: the end of privacy -- I'll have what Mrs. Morgenson is having: the most powerful hidden persuader of them all: us.
Includes bibliographical references (p. [261]-284) and index.
Keywords: Consumer behavior; Consumers -- Psychology; Brand choice -- Psychological aspects; Marketing -- Psychological aspects; Neuromarketing